2017
DOI: 10.5455/medarh.2017.71.148-150
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Side Effect Related With Anti-Tumor Necrosis Factor Alpha Treatment

Abstract: Introduction:Anti-tumor necrosis factor (anti-TNF) treatments are effective in controlling disease activity in many immune-mediated diseases such as psoriasis and ankylosing spondylitis (AS). Although side effects such as infection and skin reactions are predictable in anti-TNF treatment; susceptibility to psoriasis is considered as a paradoxical side effect.Case report:We report a case of forty-year-old male patient with 7 years of AS was taking anti-TNF therapy. He admitted our clinic with widespread guttate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Proportion rates of 44.8% and 36.3% for plaque and palmoplantar pustular psoriasis, respectively, were reported in the review by Brown et al, contrasting with a proportion of 49% for plaque and of 52% for palmoplantar pustular in the review from Collamer et al An estimated incidence rate of anti-TNF-α triggered psoriasiform dermatoses of 1.04-3.00/1000 person-years has also been reported in the literature, with infliximab as the most frequent anti-TNF-α involved, followed by adalimumab, making psoriatic dermatoses the most frequent form of PR and exceeding psoriasis prevalence among the general population (around 2%) 6,7 . Iborra et al reported the prevalence of this side effect as between 1.5% and 5% in patients who were using anti-TNF-α due to IBD 4 .…”
Section: Paradoxical Psoriasismentioning
confidence: 99%
See 3 more Smart Citations
“…Proportion rates of 44.8% and 36.3% for plaque and palmoplantar pustular psoriasis, respectively, were reported in the review by Brown et al, contrasting with a proportion of 49% for plaque and of 52% for palmoplantar pustular in the review from Collamer et al An estimated incidence rate of anti-TNF-α triggered psoriasiform dermatoses of 1.04-3.00/1000 person-years has also been reported in the literature, with infliximab as the most frequent anti-TNF-α involved, followed by adalimumab, making psoriatic dermatoses the most frequent form of PR and exceeding psoriasis prevalence among the general population (around 2%) 6,7 . Iborra et al reported the prevalence of this side effect as between 1.5% and 5% in patients who were using anti-TNF-α due to IBD 4 .…”
Section: Paradoxical Psoriasismentioning
confidence: 99%
“…Inflammatory bowel disease (ulcerative colitis and Crohn's disease) has also been described by several authors as a PR to biologic therapy, with a prevalence of around 43 times higher than in the general population 1,2,4 . In the available literature, it is mostly associated with etanercept in reports concerning juvenile idiopathic arthritis and other inflammatory rheumatic conditions like ankylosing spondylitis, presenting in the form of Crohn's disease.…”
Section: Paradoxical Inflammatory Bowel Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…However, long-term use of these drugs can lead to immunocompromise, bone marrow suppression, liver and kidney function damage, gastrointestinal dysfunction, and cartilage degeneration [12]. Although TNF-α inhibitors are currently the most used biological agent in the treatment of RA, they may lead to infection [13]. erefore, it is urgent to find effective drugs with low toxicity to treat RA.…”
Section: Introductionmentioning
confidence: 99%